STRATEGY BRAND REPOSITIONING DALAM MENINGKATKAN CITRA MEREK LE’PARADIS - Chynthia Evelyne (Jurnal Performa)
It is important for a company to have a brand identity, because brand identity is a considerable force in business. It does not only distinguish a business from another, but it becomes an intangible asset for companies to gain profit. Positioning is defined as the consumer's impression towards a certain brand. Proper positioning means that the brand is well accepted by the consumers. Le'Paradis engages in the food and beverage industry, or more specifically, in baked goods business. The company realizes that the company's positioning is not right. As a result, the company's values do not reach the consumers. The purpose of this research is to determine the most suitable repositioning strategy to improve the brand image of Le'Paradis. This research is a qualitative research. The data collection methods used in this study are structured interviews and documentation, while purposive sampling is used to select informants. Research results indicate that the best repositioning strategy for Le'Paradis can be performed by determining the target market, finding functional benefits of the product offered, and providing experience benefits to consumers. The objective of this strategy is to make consumers realize that Le'Paradis' product is different from its competitors